Real-time grid optimisation through digitalisation – results of the STORM project. (September 2018) - Johansson, C.; Vanhoudt, D.; Brage, J.; Geysen, D.
Abstract: The STORM controller is a platform for operational demand side management and has been developed since 2015 as part of the Horizon 2020 project STORM. The controller has been developed using state-of-the-art solutions based on machine learning and applied artificial intelligence, and it has already spawned results now being used in commercial smart heat grid projects throughout Europe. The results show significant benefits relating to peak load management, distribution balancing and market interaction mechanisms.